Persistence and geochemical differentiation of drilling waste in unconsolidated deep-sea sediments from the Ulleung Basin, East Sea - Jong-Hwa Chun; In Kwon Um; Yong Hoon Kim (Marine Pollution Bulletin, 2026)

A structurally controlled mega-pockmark on the southwestern continental shelf of the East Sea (Sea of Japan) - Deniz Cukur; Gee-Soo Kong; In-Kwon Um; Byoung-Yeop Kim (Marine Geology, 2026)

Integrated controls on the labile biogenic silica distribution in a muddy land–shelf continuum - Yunji Kim; Hoi Soo Jung; Jeongwon Kang; In Kwon Um; Seok Jang; Byung-cheol Kum (Regional Studies in Marine Science, 2026)

Phase-consistent broadband synthesis of shallow marine seismic data using complementary seismic sources - Jiho Ha; Jungkyun Shin; Deniz Cukur; In-Kwon Um (Acta Geophysica, 2026)
Shallow marine seismic surveys commonly rely on portable seismic sources such as small air-gun and high-frequency sparker sources, each characterized by distinct frequency content and imaging capabilities. While air-guns provide superior penetration depth and structural continuity, sparkers offer high vertical resolution for shallow subsurface imaging. Integrating these complementary datasets to obtain broadband seismic responses remains challenging, primarily due to differences in source wavelets and phase characteristics. This study proposes a phase-consistent broadband seismic synthesis method for a shallow marine coastal area, based on simultaneously acquired small air-gun and sparker data along the same survey line. To ensure physical consistency prior to synthesis, deterministic pre-processing steps were applied, including source wavelet estimation, de-bubbling, de-signature, and band-limited spectral whitening. Phase alignment was then achieved using a convolution-based approach, where the air-gun source wavelet served as a low-frequency-stable reference. Multiple candidate reference wavelets were examined, and the applicable frequency band was selected for synthesis. The resulting broadband seismic section demonstrates improved reflector continuity and enhanced shallow resolution without phase distortion, compared to the individual datasets. Spectral analysis confirms balanced frequency band expansion. The results highlight that phase consistency is a critical prerequisite for physically meaningful broadband synthesis and demonstrate the effectiveness of the proposed method for shallow marine seismic imaging.

Machine-learning-based semi-quantitative analysis model of clay minerals in Onsan–Busan coastal sediments, South Korea - Ju Young Park; Yesung Jo; Hyo Jin Koo; In Kwon Um; Kyungbook Lee (Geosciences Journal, 2026)

Fine-grained surface sediment provenance in the Hupo Basin, Eastern Coast of Korea - In Kwon Um; Man Sik Choi; Jang-Jun Bahk; Soo Yeon Han (Geo-Marine Letters, 2026)

Calibration of sortable silt mean size to bottom current speeds in the East Sea (Japan Sea): challenges and prospects - Jang-Jun Bahk; Gyutae Sim; Haedo Baek; Dong Eun Lee; In-Kwon Um (Geo-Marine Letters, 2026)

Current contamination trends and historical records of traditional and emerging polycyclic aromatic hydrocarbons in sediments from Yeongil Bay and Hupo Region, East Sea - Jihyun Cha; Chang-Eon Lee; Mungi Kim; Youngnam Kim; Jiyun Gwak; Dong Jin Joe; Jae-Hyun Lim; In Kwon Um; Man Sik Choi; Seongjin Hong (Marine Pollution Bulletin, 2026)

Dispersion of metal contaminants from the coast to offshore on the southeastern coast of Korea - In Kwon Um; Man Sik Choi; Dasom Yang; Minjae Lee (Marine Pollution Bulletin, 2025)

Tsunami hazard potential of submarine landslides in the southwestern East Sea (Sea of Japan) - Deniz Cukur; Xiaoming Wang; Aaron Micallef; Senay Horozal; In-Kwon Um; Gee-Soo Kong; Seong-Pil Kim; Yaoru Liu (Natural Hazards, 2025)

Tectonic evolution of the northeastern Korean continental margin as a transform margin associated with the East Sea back-arc opening - Hojun Kim; Young Jae Shinn; In Kwon Um (Journal of Asian Earth Sciences, 2025)

Spatial variations in organic matter sources and biogeochemical processes in the East Sea - Jiyoung Choi; Bo-Yeon Yi; Yuri Kim; Eun-Je Jeong; In-Kwon Um (Frontiers in Marine Science, 2025)
In this study, the spatial variations in total organic carbon (TOC), stable carbon isotopes (δ¹³Corg), C/N ratios, and nitrogen isotopes (δ¹⁵Norg) in East Sea sediments are examined to elucidate the sources, preservation, and diagenetic processes of organic matter. To this end, surface sediment samples were collected from the coastal regions of the East Sea using a box corer and analyzed for TOC, TON, stable isotopes (δ¹³C, δ¹⁵N), and grain size. The study region is categorized into three zones based on sediment characteristics: Zone A (straits), Zone B (northern coastal regions), and Zone C (central Ulleung Basin). Zone A, characterized by coarse sediments and dynamic hydrodynamic conditions, exhibits the lowest TOC (0.67%) and enriched δ¹³Corg values (-20.67‰). Zone B, influenced by coastal inputs, has moderate TOC (2.09%), slightly depleted δ¹³Corg (-21.09‰), and higher C/N ratios (6.30). Zone C, dominated by fine-grained mud sediments, features slightly lower TOC (1.96%), along with the most depleted δ¹³Corg (-21.86‰). Stable isotope analyses reveal that autochthonous particulate organic matter (POM) from marine phytoplankton is the primary source of organic matter in the East Sea. δ¹³Corg values (-23.15‰ to -20.33‰) align with phytoplankton-derived POM (-25‰ to -22‰), highlighting significant marine primary production contributions. In contrast, allochthonous inputs from atmospheric deposition, the Tsushima Warm Current, and rivers contribute approximately 82 gC/m²/year compared to 273 gC/m²/year from autochthonous sources. Seasonal δ¹³C variations are strongly correlated with peaks in primary productivity during spring and autumn. The study reveals differences between coastal (Zone B) and offshore (Zone C) regions in productivity regimes, nutrient utilization, and depositional settings. Coastal regions with high productivity show enriched δ¹³Corg, while offshore areas preserve isotopically lighter organic matter owing to stable depositional environments. Understanding the biogeochemical processes in the East Sea is essential for elucidating carbon cycling and its ecosystem implications. As a marginal sea with unique sedimentary dynamics, the East Sea serves as a natural laboratory for studying organic matter preservation. The findings provide insights into past and present carbon cycling and support predictions of future environmental changes under shifting climatic conditions.

Development of shallow-water contourite deposits on the muddy continental shelf off southeastern Korea - Jong-Hwa Chun; Jiho Ha; Jungkyun Shin; In-Kwon Um (Geo-Marine Letters, 2025)

3D UHR seismic and back-scattering analysis for seabed and ultra-shallow subsurface classification - Jiho Ha; Jungkyun Shin; Kyoungmin Lim; In-Kwon Um; Boyeon Yi (Acta Geophysica, 2024)
Recently, the seabed classification method based on back-scattering data of multi-beam echo-sounder (MBES) is widely used to analyze the distribution of seabed sediment. Although various analysis methods for seabed classification using multi-spectral MBES have been developed, they are limited in securing penetration depth to consider the characteristics of the shallow subsurface structure. In this study, the seabed and ultra-shallow subsurface classification was performed by comparative analysis of box corer sampling, back-scattering, and 2D/3D ultra-high-resolution (UHR) seismic data obtained from Yeongil Bay, South Korea. We proposed a process for seismic ultra-shallow subsurface classification by the segmentation of the primary seabed reflection wavelet and the amplitude analysis. The seabed-reflected amplitude and back-scattering intensity showed similar mapping trends in the relatively homogeneous and thick surface sediment. On the other hand, it was confirmed that back-scattering data and seabed-reflected amplitude show different patterns when the subsurface structure is related to the seabed surface. It is presumed that because seismic data containing relatively low-frequency components have a deeper penetration depth than MBES, they contain more characteristics of the ultra-shallow subsurface than back-scattering data. These were determined that back-scattering has advantages in representing acoustic anomaly distribution by surface sediment type, and seabed-reflected amplitude is advantageous for representing sediment type by ultra-shallow subsurface. In particular, these results were well shown when the surface sediment thinly covered the rocky bottom. Therefore, it is necessary not only to analyze the back-scattering of MBES but also the ultra-shallow subsurface features through seismic data for valid seabed classification.

Revisiting elemental geochemistry in surface sediments of the Ulleung Basin, East/Japan Sea: Signals from ocean dumping materials - In Kwon Um; Man Sik Choi; Soo Yeon Han; Seonghu Choi; Dasom Yang (Marine Pollution Bulletin, 2024)

Submarine landslides on the Eastern South Korea Plateau (ESKP)—Do pumice-rich tephra layers control slope stability? - Deniz Cukur; In-Kwon Um; David M. Buchs; Seong-Pil Kim; Gee-Soo Kong; Jong-Hwa Chun; Senay Horozal; Seok-Hwi Hong; Shin Yu; Tae-Yeon Kim (Marine Geology, 2024)

Depositional history of the subaqueous delta off the southeastern coast of Korea during the post-glacial period - Eun-Je Jeong; Jang-Jun Bahk; In-Kwon Um; Gwang-Soo Lee; Boyeon Yi (Marine Geology, 2023)

Factors for pre-conditioning and post-failure behaviour of submarine landslides in the margins of Ulleung Basin, East Sea (Japan Sea) - Senay Horozal; Jang-Jun Bahk; Deniz Cukur; Roger Urgeles; David M. Buchs; Sang Hoon Lee; In-Kwon Um; Seong-Pil Kim (Marine Geology, 2023)

Field application of 3D CHIRP for geological surveys of shallow coastal regions - Jungkyun Shin; Jiho Ha; Jong-Hwa Chun; In-Kwon Um (Marine Geophysical Research, 2022)

Use of Pb Isotopes to Track the Sources of Sediment Metals in Youngil Bay, Korea and Offshore - Yunho Song; Man Sik Choi; In Kwon Um; Seonghu Choi; Dongjin Cho; Sojeong Park; Minseok Choi (Ocean Science Journal, 2022)

Fucoxanthin biosynthesis has a positive correlation with the specific growth rate in the culture of microalga Phaeodactylum tricornutum - Do Yeon Kwon; Trang Thi Vuong; Jaeyoung Choi; Taek Sung Lee; Jae-In Um; Song Yi Koo; Keum Taek Hwang; Sang Min Kim (Journal of Applied Phycology, 2021)

Latest Quaternary mass-transport processes of fan-shaped body in the western margin of the Ulleung Basin, East Sea (Japan Sea) - Sang-Hoon Lee; Hyeong-Tae Jou; Jang-Jun Bahk; Hyunggu Jun; Seong-Hoon Moon; Han-Joon Kim; Senay Horozal; Deniz Cukur; In-Kwon Um; Dong-Geun Yoo; Roger Urgeles (Geosciences Journal, 2021)

Contrasting developments of Pleistocene calcareous clay units in the middle Bengal Fan and their implications for paleoenvironmental changes - Jang-Jun Bahk; In-Kwon Um; Kyung-Hoon Shin (Geosciences Journal, 2019)

Tsunami hazard from submarine landslides: scenario-based assessment in the Ulleung Basin, East Sea (Japan Sea) - Roger Urgeles; Jang-Jun Bahk; Sang-Hoon Lee; Senay Horozal; Deniz Cukur; Seong-Pil Kim; Gil-Young Kim; Sueng-Won Jeong; In-Kwon Um (Geosciences Journal, 2019)

A multi-factor approach for process-based seabed characterization: example from the northeastern continental margin of the Korean peninsula (East Sea) - Deniz Cukur; In-Kwon Um; Jong-Hwa Chun; So-Ra Kim; Gwang-Soo Lee; Yuri Kim; Gee-Soo Kong; Senay Horozal; Seong-Pil Kim (Geo-Marine Letters, 2018)

Variability in Particle Mixing Rates in Sediments with Polymetallic Nodules in the Equatorial Eastern Pacific as Determined from Measurements of Excess 210Pb - Kiseong Hyeong; Inah Seo; Hyun-Bok Lee; Chan Min Yoo; Sang-Bum Chi; In Kwon Um (Ocean Science Journal, 2018)

Provenance of Fine-grained Sediments in the Inner Shelf of the Korea Strait (South Sea), Korea - In kwon Um; Man Sik Choi; Sung Ho Bae; Yunho Song; Gee Soo Kong (Ocean Science Journal, 2018)

Geophysical evidence and inferred triggering factors of submarine landslides on the western continental margin of the Ulleung Basin, East Sea - Deniz Cukur; Seong-Pil Kim; Gee-Soo Kong; Jang-Jun Bahk; Senay Horozal; In-Kwon Um; Gwang-Soo Lee; Tae-Soo Chang; Hun-Jun Ha; David Völker; Jung-Ki Kim (Geo-Marine Letters, 2016)

Factors controlling typhoons and storm rain on the Korean Peninsula during the Little Ice Age - Kota Katsuki; Dong-Yoon Yang; Koji Seto; Moriaki Yasuhara; Hiroyuki Takata; Masashi Otsuka; Toshimichi Nakanishi; Yoonyeol Yoon; In-Kwon Um; Richard C. W. Cheung; Boo-Keun Khim; Kaoru Kashima (Journal of Paleolimnology, 2016)

Origin and depositional environment of fine-grained sediments since the last glacial maximum in the southeastern Yellow Sea: evidence from rare earth elements - In Kwon Um; Man Sik Choi; Gwang Soo Lee; Tae Soo Chang (Geo-Marine Letters, 2015)

Sedimentation and seafloor mound formation in the southern slope of the Ulleung Basin, East Sea, Korea, since the Last Glacial Maximum - Jang Jun Bahk; Dong Geun Yoo; In kwon Um; Sang Hoon Lee; Kyung Sik Woo (Geosciences Journal, 2013)